Aplikasi Silika Gel dalam Fraksinasi Senyawa Bioaktif dari Tanaman Obat - Muhammad Rezky Wahyudi; Jannatun Nisa; Maulida Maulida; Maura Putri Ariqah; M. Jian Prayoga; Nicky Saputra; Noor Kamalliyah (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Silica gel is one of the most commonly used adsorbents in the fractionation of bioactive compounds from medicinal plants. This is due to its ability to separate compounds based on differences in polarity, thus simplifying the purification process of active components. Fractionation itself is a crucial step in phytochemical research, as it aims to obtain active compounds in a purer, standardized form, and ready for further testing, both biologically and pharmacologically. This study aims to review the effectiveness of silica gel in the fractionation of active compounds from various types of medicinal plants. The study was conducted through a systematic literature review method with a qualitative-descriptive approach to 35 scientific articles published in the last five years. The articles analyzed were those that presented primary data on the use of silica gel in the fractionation process of medicinal plants. The results of the study showed that silica gel was proven effective in separating various polar compounds such as flavonoids, alkaloids, and phenolic compounds from crude extracts of medicinal plants. Some studies have even succeeded in isolating pure compounds that have significant biological activities, such as antioxidants, antimicrobials, and anti-inflammatory. The effectiveness of fractionation with silica gel is influenced by several important factors, such as the type and composition of the solvent, the elution technique (gradient or isocratic), and the support of advanced analytical methods such as thin-layer chromatography (TLC) and spectroscopy (UV-Vis, FTIR, and NMR). However, the use of silica gel still has several limitations, including the relatively high solvent requirements and long elution times. From the results of this study, it can be concluded that silica gel has great potential in supporting the fractionation process and isolation of bioactive compounds from medicinal plants. Therefore, optimization of silica gel-based fractionation techniques is important to support research and development of more efficient, standardized, and sustainable phytopharmaceutical products.